Development of a scale to measure cool brands - Lopes, Rui Alexandre Sousa (2012)
The meaning of cool brands has attracted the attention of many marketing practitioners, but little attention has been given in academia. This study reports the development of a scale measuring characteristics of cool brands and the model is grounded in the accepted paradigm for scale development provided by Churchill (1979). Based on an exploratory qualitative and quantitative analysis (two national samples), a seven-dimension scale of a cool brand is identified: contemporary, singularity, remarkable experience, sub-group, social conscience, classic and preciousness. Construct, nomological and predictive validity is examined, and the relationship of the scale with important outcome variables assessed: brand credibility, consumer satisfaction, perceived quality, self-brand connection and communal-brand connection. The positive results demonstrate the validity and consistency of the scale as well as that most of the Cool Brand Characteristics dimensions were strongly associated with the outcome variables. This dissertation concludes with a brief discussion of the implications of the study for future research and marketing practicesl.